RESEARCH OF VEGETATIVE MECHANISMS OF NEGATIVE EMOTIONAL STATES’ DEVELOPMENT AND REGULATION AMONG TEENAGERS (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
Vegetative mechanisms of negative emotional states’ development and regulation, in experimentally modelled negative psychoemotional environment at teenagers are investigated. Dependence of dynamic changes of vegetative regula-tion of cardiovascular system on gender and self-appraisal level of examinees under the influence of negative psychoemotional environment is revealed.
Keywords: emotional states; teenagers; gender and self-appraisal level; cardiovascular system